‘A Community Under Siege’: Analysing Kohut’s Thoughts of ‘Narcissistic Rage’ in Githa Hariharan’s Fugitive Histories - Midya, Somsuvra; Mishra, Binod (International Journal of Language and Literary Studies, 2024)
This paper looks at the operational mechanics of narcissistic rage as a subversive force within the poignant depiction of communal violence in Githa Hariharan’s novel Fugitive Histories, utilizing a psychoanalytical lens inspired by the insights of Kohut. This exploration aims to unravel the intricate nexus between the phenomenon of riot and narcissistic tendencies, scrutinizing the concept of collective narcissism as it pertains to social communities. Employing Kohut’s in-depth study of group psychology, the research delves into the transformative dynamics of narcissistic rage and its consequential impact on instances of communal upheaval. The paper culminates in a discussion highlighting the potential role of empathy as a mitigating agent against the perils of narcissistic rage.